Balance Analysis of Peripheral Neuropathy in Type 2 Diabetes Mellitus Based on Logistic Regression Equation - Zhang, Lixin; Du, Qianqian; Yao, Manman; Wang, Mai; Ge, Bing (Scanning, 2022)
This paper analyzes the factors of peripheral neuropathy in type 2 diabetes mellitus and puts forward a balanced analysis of peripheral neuropathy in type 2 diabetes mellitus based on logistic regression equation. A total of 1192 eligible patients were selected as the study subjects. All selected patients underwent 75 g oral glucose tolerance test to measure fasting blood glucose and insulin and 2-hour postprandial blood glucose and 2-hour postprandial insulin, as well as neuroelectrophysiological examination. The results showed that the OR values of age, course of disease, fingertip blood glucose immediately after admission, and 2-hour blood glucose were greater than 1, and the P values were all less than 0.05, which were the risk factors of diabetic peripheral neuropathy. OR value of β cell function index (HBCI) is less than 1. P is less than 0.05, and it is a protective factor of diabetic peripheral neuropathy. Laboratory indicators are as follows: 75 g OGTT: 0-hour blood glucose, 2-hour blood glucose, and glycosylated hemoglobin; serum creatinine; glutamate transaminase; fibrinogen; ten items of hemoglobin; and indexes reflecting islet function: islet β is thin, and there are significant differences in cell function index, insulin resistance index, and insulin secretion index between the non-DPN group and DPN group. Age, course of disease, fingertip blood glucose immediately after admission, and blood glucose within 2 hours after admission were the risk factors for diabetic peripheral neuropathy. Islet β cell function index (HBCI) is a protective factor of diabetic peripheral neuropathy.